Hemodialysis for treatment of levofloxacin‐induced neurotoxicity. Issue 2 (25th September 2018) - Idrees, Najia; Almeqdadi, Mohammad; Balakrishnan, Vaidyanathapuram S.; Jaber, Bertrand L.
Abstract: Levofloxacin, a third‐generation fluoroquinolone antibiotic, is rarely associated with neurotoxicity. Patients with advanced kidney disease are particularly vulnerable to this adverse effect. We present two elderly patients with kidney failure who developed levofloxacin‐induced neurotoxicity, which was successfully treated with frequent hemodialysis, resulting in the full resolution of their symptoms. Neurotoxicity is a well‐known side effect of fluoroquinolone antibiotics. Postulated mechanisms include inhibition of the gamma‐aminobutyric acid A receptors and activation of the excitatory N‐methyl‐D‐aspartate receptors. Risk factors include older age, kidney disease, pre‐existing neurological disorders, and drug–drug interactions. While management of levofloxacin‐induced neurotoxicity includes discontinuation of the drug and supportive care, hemodialysis is not recommended, despite available pharmacokinetic data in support of its dialyzability. The successful use of hemodialysis for the treatment of levofloxacin‐induced neurotoxicity observed in our two patients with kidney failure should be further considered for rapid resolution of this rare fluoroquinolone‐related adverse effect in patients with impaired kidney function.